MECABOT: A Home Security Smart Phone Robot - Sohani, Tejas; Sharma, Aayush; Sharmila Agnal, A. (Asian Journal of Science and Applied Technology, 2018)
Now a day’s home security is a critical issue in society. An android controlled locomotive robot platform, developed in order to enhance home security. The drive mechanism consists of 3 differential locomotive modes, with 2 steerable and 4 derivable wheels. MECABOT is controlled by 2.4 GHz short range radio frequency band. The data is transmitted using a frequency hopping spread spectrum of Bluetooth technology. Motor driver with PWM (Pulse Width Modulator) is used to control motor power and direction. The data transmitted to control robot is send by an android app inbuild facility of Bluetooth. In this system the mobile robot platform was developed using Android and Arduino environment.